Ecosystem services from combined natural and engineered water and wastewater treatment systems: Going beyond water quality enhancement - Zawadzka, Joanna Ewa; Gallagher, Elaine; Smith, Heather M.; Corstanje, Ronald (Elsevier, 2019)
Combined natural and engineered water and waste water systems (cNES) are nature-based solutions that utilise naturally occurring processes to remove impurities from water and therefore contribute to the ecosystem service of water quality enhancement. We hypothesise that these systems may also have a potential to deliver ecosystem services other than their primary purpose of water purification and we use spatially-explicit modelling tools to determine these benefits. We focused on three different types of cNES: bank filtration (BF), managed aquifer recharge/soil aquifer treatment (MAR/SAT), and constructed wetlands (CW), and combined the ecosystem services cascade, DESSIN and CICES conceptual frameworks with multiple InVEST 3.4.4 models to investigate the spatial distribution of intermediate ecosystem services within the sites as well as in the surrounding landscape. We also determined the role of habitats present within the sites in wider landscape’s connectivity to the nearest Natura 2000 areas using the Circuitscape 4.0 model, assessed the public perception of the aesthetic value of two of the cNES technologies, i.e. CW and MAR/SAT, via an online survey, and linked the determined ecosystem services to their likely beneficiaries. Our results indicated that the sites characterised with semi-natural ecosystems had a good potential for ecosystem services provision and that the selected cNES technologies were favourably received by the public as compared to their engineered equivalents. We concluded that determination of ecosystem services potential from nature-based solutions, such as cNES technologies, should be done in consideration of various contextual factors including the type of habitats/ecosystems present within the proposed solutions, the location within the landscape as well as properties and ecosystem services potential of the areas surrounding the sites, all of which can be facilitated by deployment of spatially-explicit ecosystem service models at early stages of the planning process.
Keywords: Ecosystem services; Habitat connectivity; Nature-based solutions; Water and waste water treatment; InVEST models; Circuitscape